Excess 40Ar in Alkali Feldspar and 206,207Pb in Apatite Caused by Fluid-Induced Recrystallisation in a Semi-Closed Environment in Proterozoic (Meta)Granites of the Mt Isa Inlier, NE Australia - Daniil Popov; Richard Spikings; André Navin Paul; Maria Ovtcharova; Massimo Chiaradia; Martin Kutzschbach; Alexey Ulianov; Gary O’Sullivan; David Chew; Kalin Kouzmanov; Eszter Badenszki; J. Stephen Daly; et al. (Geosciences)
Interpretation of 40Ar/39Ar dates of alkali feldspar and U-Pb dates of apatite depends on the dominant mechanism of isotopic transport in these minerals, which can be either diffusion or fluid-assisted dissolution-reprecipitation. To clarify the contributions of these processes, we have conducted a holistic study of alkali feldspar, apatite and other minerals from the Mt. Isa Inlier in NE Australia. Mineral characterisation by electron microscopy, optical cathodoluminescence imaging and element mapping reveal a complex interplay of textures resulting from magmatic crystallisation, deuteric recrystallisation, local deformation with subsequent higher-temperature alteration, and finally ubiquitous low-temperature alteration. U-Pb and Pb isotopic data for zircon, apatite, fluorite and alkali feldspar suggest that the latter event occurred at ~300 Ma and was associated with fluid-assisted exchange of Pb isotopes between minerals in the same rock, causing some apatite grains to have 207Pb-corrected U-Pb dates that exceed their crystallisation age. However, this event had no unequivocal effect on the 40Ar/39Ar or Rb-Sr systematics of the alkali feldspar, which were disturbed by higher-temperature alteration at ~1450 Ma. The age of the latter event is derived from Rb-Sr data. 40Ar/39Ar dates are very scattered and suggest that 40Ar redistribution proceeded by diffusion in the presence of traps in some places and by dissolution-reprecipitation with variable amounts of recycling in other places. Our results demonstrate the complex effects that interaction with limited amounts of fluids can have on 40Ar/39Ar dates of alkali feldspar and U-Pb dates of apatite and thereby reinforce previous critique of their suitability for thermochronological reconstructions. We further identify and discuss potential implications for noble gas geochronology of groundwaters and fission track dating of apatite.